72 Dangerous student passenger drop-off, pedestrian behaviours and the built environment near schools. (1st September 2016) - Rothman, Linda; Howard, Andrew; Buliung, Ron; Richmond, Sarah A; Macarthur, Colin; Macpherson, Axlison
Abstract : Background: Dangerous drop-off of student passengers and pedestrian behaviours near schools have not been well described despite the potential for pedestrian motor vehicle collisions (PMVC). Safe environments are required for children around schools. Passenger drop-off and child pedestrian behaviours are described by occurrence of child PMVC and built environment (BE) features in Toronto, Canada. Methods: Dangerous passenger drop-off and pedestrian behaviours observations were done in 2015. Child PMVCs from 2000–2013, age 4–12 years, were mapped near 100 schools. Case schools had > 1 collision and control schools had 0. Dangerous driving/parking, unsafe pedestrian crossings, distracted walking and disobeying crossing controls/guards were compared using chi-square statistics by case/control status or BE features: downtown/inner suburbs, school crossing guards and designated car drop-off areas. Results: Dangerous drop-off and/or pedestrian behaviours occurred at over 92% of schools. A greater proportion of case schools had children crossing at uncontrolled midblocks (97% vs. 78% controls). A greater proportion of inner suburb schools versus downtown had cars double-parked (52% vs. 28%) and parked blocking crossing controls (25% vs. 4%). A smaller proportion of schools with crossing guards versus without had cars parked blocking crossing controls (10% vs. 25% without) and drivers texting (5% vs. 22%). A smaller proportion of schools with designated drop-off areas versus without, had cars reversing dangerously (76% vs. 55%), parked blocking crossing controls (31% vs. 10%), children crossing at uncontrolled midblocks (78% vs. 95%) and between parked cars (48% vs. 76%). Conclusions: Dangerous student drop-off and pedestrian behaviours were pervasive at schools. Occurrence of behaviours was related to the BE; particularly designated car-drop off areas. Adaptations to the BE near schools may defer dangerous behaviours and provide a safer child pedestrian environment.